Globalization, pedagogy and international literature for children and young adults - Adhikari, Hari R (Bodhi: An Interdisciplinary Journal, 2012)
DOI: http://dx.doi.org/10.3126/bodhi.v4i1.5812 Bodhi 2010 4(1): 81-99